On-chip hotplate for temperature control of CMOS SAW resonators - Nordin, Anis Nurashikin; Voiculescu, Ioana; Zaghloul, Mona E. (2008)
Due to the sensitivity of the piezoelectric layer in surface acoustic wave (SAW) resonators to temperature, a method of achieving device stability as a function of temperature is required. This work presents the design, modeling and characterization of integrated dual-serpentine polysilicon resistors as a method of temperature control for CMOS SAW resonators. The design employs the oven control temperature stabilization scheme where the devicepsilas temperature is elevated to higher than Tmax to maintain constant device temperature. The efficiency of the polysilicon resistor as a heating element was verified through a 1-D partial differential equation model, 3-D CoventorWarereg finite element simulations and measurements using Compixreg thermal camera. To verify that the on-chip hotplate is effective as a temperature control method, both DC and RF measurements of the heater together with the resonator were conducted. Experimental results have indicated that the TCF of the CMOS SAW resonator of -97.2 ppm/degC has been reduced to -23.19 ppm/degC when heated to 56degC.